EVALUATION OF THE GENETIC VARIABILITY OF SHIHUAHUACO Dipteryx ferrea (Ducke) Ducke IN THE PERUVIAN AMAZON, USING MICROSATELITES MARKERS - DIAZ SORIA, Rossana (2019)
We studied the genetic variability of Dipteryx ferrea shihuahuaco in seven natural populations from the Peruvian Amazon using nine microsatellite loci. The results showed a high genetic diversity shown by the high polymorphism (total alleles = 135, mean alleles per locus = 15 ± 6 alleles) and allelic richness (Macuya = 11 and Iñapari = 8, maximum and minimum allelic richness, respectively). The analysis of principal components showed a strong overlap among the populations, which added to the low values of interpopulation genetic distance (from 0.07 to 0.10), reveals a high genetic similarity among populations. The dendrogram based on the genetic distance of Shared Allele showed populations clustered in three main groups, the first formed by Manu and Iñapari populations (group A, bootstrap = 91%), the second by Contamana and Macuya (group B, 60%), and the third by Tamaya, Santa Clara e Inuya (group C, 100%). The correlation analysis showed that there is a positive correlation between geographic distance and genetic distance among pairs of populations (r = 0.62, p<0.005). The high genetic similarity among populations found in this species can be attributed to the allogamous reproduction system (cross-pollination) of Shihuahuaco, to its pollinators (bats, bees) and dispersers (macaws, eagles, peccaries, etc.) that can travel long distances, which facilitates the gene flow among populations. Historical factors such as the tectonic activity of the study area also influenced the genetic relationships observed among the populations, distinguishing closely related genetic groups such as A and B that cover a large part of the geographical distribution of the species and a differentiated group (group C) located in a more recent developed area in the department of Ucayali.